True Fruits - Carvalho, Luis, active 2013, (SAGE Knowledge. Cases., 2013)
The case focuses on True Fruits, a leading smoothie producer in Germany. The founders Marco Knauf, Inga Koster and Nicolas Lecloux spent their exchange semester in 2005 in Scotland where they discovered smoothies. In their homeland Germany they could not find smoothies in supermarkets and decided to start their own smoothie company. The trio's aim was to make the most desirable non-alcoholic drink in Germany and to build their business on quality, authenticity and lifestyle. In 2006 they incorporated True Fruits. They found the right bottler for their smoothies and soon supermarkets were stocking them. From then on the company grew exponentially until they sold over half a million smoothies per month by 2008. They also expanded to Austria and Switzerland. By 2010 competition from other brands was on the rise and supermarkets were negotiating sharply over prices. True Fruits had to decide what their strategy for the future would be. The options were internationalization, expanding production, or expanding the product range.The case addresses factors in start-up hurdles with regards to manufacturing and financing. It also addresses product placement, internationalization and the diversification of a product portfolio.